Freiheit nach Kant, Tradition, Rezeption, Transformation, Aktualität. - Saša Josifović; Jörg Noller (Editors) (Critical Studies in German Idealism, 2019)
Kant's conception of freedom is of special importance in the history of philosophy. It not only brings together older traditions but has great influence on later theories of freedom. The edited volume analyzes Kant's theory, referring to the concepts of will, choice, autonomy, and reason. It consists of four parts: Kant's theory in its historical context; Kant's own conception as developed in his various philosophical works; central conceptions of freedom in German Idealism after Kant (including Reinhold, Schiller, Maimon, Jacobi, Fichte, Schelling, Hegel, Schopenhauer); the systematic relevance of Kant's conception of freedom with regard to recent debates in analytic philosophy (agent causality, compatibilism and incompatibilism).